2018
DOI: 10.1037/pha0000203
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of tobacco and alcohol co-use from ages 15 to 32: The Amsterdam Growth and Health Longitudinal Study.

Abstract: Tobacco and alcohol are often used in tandem over time, but specific predictors of course and patterns of course over time need explication. We examined differences in alcohol and tobacco course among an adolescent population as they transitioned into young adulthood across a 17-year period. Data came from participants (n = 303 for ages 15-21, n = 196 for ages 21 to 32; 52% female and 54% female, respectively) enrolled in the Amsterdam Growth and Health Longitudinal Study, an epidemiologic investigation examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 68 publications
1
2
0
Order By: Relevance
“…This is also the case with the pooled smoking prevalence among HIV positive men in 28 LMICs (24%) by Mdege and colleagues [9]. Since our study focused only on PLWH who are heavy alcohol drinkers, the higher smoking prevalence found in our study is likely to be due to the close association between alcohol use and smoking reported by several studies both in South Africa and globally [5, 17, 18, 27].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This is also the case with the pooled smoking prevalence among HIV positive men in 28 LMICs (24%) by Mdege and colleagues [9]. Since our study focused only on PLWH who are heavy alcohol drinkers, the higher smoking prevalence found in our study is likely to be due to the close association between alcohol use and smoking reported by several studies both in South Africa and globally [5, 17, 18, 27].…”
Section: Discussionsupporting
confidence: 76%
“…A study of tobacco smoking and alcohol use among PLWH conducted in Nepal found drinking alcohol to be more likely associated with current tobacco smoking among PLWH [17]. A correlation between alcohol and tobacco use has also been found in the general population [18]. High rates of depressive episodes have been reported by PLWH.…”
Section: Introductionmentioning
confidence: 99%
“…and colleagues stated that they found women to be more likely to co-use tobacco and alcohol, and they hypothesized that women in their sample were wealthier and more socially and financially independent (Ho et al, 2021). However, other studies have found that males are more likely to co-use (Kim et al, 2019;McPherson et al, 2018). One explanation for these previous studies may be that women and men who work and have a stable income have greater access to purchasing these substances, resulting in greater use (Anand & Roy, 2016).…”
Section: Discussionmentioning
confidence: 97%